The effects of different warm-up exercises on throwing velocity in handball players - Zecchin, Arthur; Soto, Diego; Fernandez Fernandez, Jaime; Santos, Luis; Foster, Carl; Boullosa, Daniel (International Journal of Sports Medicine)
We investigated the effect of plyometric and isometric warm-up exercises on handball throwing velocity and verified the relationships between strength measures and throwing velocity. Sixteen U-22 elite male handball players (age: 19.8 ± 0.9 yrs; handball training experience: 10.5 ± 1.0 yrs), of the Spanish University Championship-winning team participated in this study. Players were assessed for maximum isometric shoulder internal rotation strength (kg), and the loads (kg) associated with 1 m/s in half squat and bench press exercises. Subsequently, they performed standardized warm-up plus isometric (ISO) vs. plyometric (PLY) vs. control (CON) exercises in randomized order followed by the evaluation of ball throwing velocity. There were no significant differences in throwing velocity following any condition. Moderate, significant correlations were observed between throwing velocity and the load associated with 1 m/s in the half squat under all conditions (r=0.56-0.61; p<0.05) and in the bench press after PLY (r=0.50; p=0.047). The CON condition which included submaximal running resulted in similar throwing velocity than the experimental conditions including strength exercises. The identified associations between the loads associated to 1 m/s in half squat and bench press exercises highlight the important role of muscle power in handball players’ throwing ability.